Ad-hoc, mobile, and wireless networks : 14th International Conference, ADHOC-NOW 2015, Athens, Greece, June 29-July 1, 2015, Proceedings /: 14th International Conference, ADHOC-NOW 2015, Athens, Greece, June 29-July 1, 2015, Proceedings. (2015) - Unknown
No abstract available